STING, a cytosolic DNA sensor, plays a critical role in atherogenesis: a link between innate immunity and chronic inflammation caused by lifestyle-related diseases. (6th July 2021) - Pham, Phuong Tran; Fukuda, Daiju; Nishimoto, Sachiko; Kim-Kaneyama, Joo-Ri; Lei, Xiao-Feng; Takahashi, Yutaka; Sato, Tomohito; Tanaka, Kimie; Suto, Kumiko; Kawabata, Yutaka; Yamaguchi, Koji; Yagi, Shusuke; et al.
Abstract: Aims: Lifestyle-related diseases promote atherosclerosis, a chronic inflammatory disease; however, the molecular mechanism remains largely unknown. Endogenous DNA fragments released under over-nutrient condition provoke sterile inflammation through the recognition by DNA sensors. Here, we investigated the role of stimulator of interferon genes (STING), a cytosolic DNA sensor, in atherogenesis. Methods and results: Apolipoprotein E-deficient ( Apoe −/− ) mice fed a western-type diet (WTD), a hypercholesterolaemic mouse model, showed higher STING expression and markers for DNA damage such as γH2AX, p53, and single-stranded DNA (ssDNA) accumulation in macrophages in the aorta compared with wild-type (WT) mice. The level of cGAMP, a STING agonist, in the aorta was higher in Apoe −/− mice. Genetic deletion of Sting in Apoe −/− mice reduced atherosclerotic lesions in the aortic arch, lipid, and macrophage accumulation in plaques, and inflammatory molecule expression in the aorta compared with the control. Pharmacological blockade of STING using a specific inhibitor, C-176, ameliorated atherogenesis in Apoe −/− mice. In contrast, bone marrow-specific STING expression in Apoe −/− mice stimulated atherogenesis. Expression or deletion of STING did not affect metabolic parameters and blood pressure. In vitro studies revealed that STING activation by cGAMP or mitochondrial DNA accelerated inflammatory molecule expression (e.g. TNF-α or IFN-β) in mouse and human macrophages. Activation of nuclear factor-κB and TANK binding kinase 1 was involved in STING-associated vascular inflammation and macrophage activation. Furthermore, human atherosclerotic lesions in the carotid arteries expressed STING and cGAMP. Conclusion: Stimulator of interferon genes stimulates pro-inflammatory activation of macrophages, leading to the development of atherosclerosis. Stimulator of interferon genes signalling may serve as a potential therapeutic target for atherosclerosis. Graphical Abstract: